Cooperating cancer-gene identification through oncogenic-retrovirus–induced insertional mutagenesis - Du, Yang (The American Society of Hematology, 2005)
Multiple cooperating mutations that deregulate different signaling pathways are required to induce cancer. Identifying these cooperating mutations is a prerequisite for developing better combinatorial therapies for treating cancer. Here we show that cooperating cancer mutations can be identified through oncogenic-retrovirus-induced insertional mutagenesis. Among 13 myeloid leukemias induced by transplanting into mice bone marrow cells infected in vitro with a replication-defective retrovirus carrying the Sox4 oncogene, 9 contained insertional mutations at known or suspected cancer genes. This likely occurred because rare bone marrow cells, in which the oncogenic retrovirus happened to integrate and in which it mutated a cooperating cancer gene, were selected because the host harbored a cooperating cancer mutation. Cooperativity between Sox4 and another gene, Mef2c, was subsequently confirmed in transplantation studies, in which deregulated Mef2c expression was shown to accelerate the myeloid leukemia induced by Sox4. Insertional mutagenesis of cooperating cancer genes by a defective oncogenic retrovirus provides a new method for identifying cooperating cancer genes and could aid in the development of better therapies for treating cancer. (Blood. 2005;106:2498-2505)